2015
DOI: 10.1128/mcb.00765-14
|View full text |Cite
|
Sign up to set email alerts
|

YAP Regulates the Expression of Hoxa1 and Hoxc13 in Mouse and Human Oral and Skin Epithelial Tissues

Abstract: c Yes-associated protein (YAP) is a Hippo signaling transcriptional coactivator that plays pivotal roles in stem cell proliferation, organ size control, and tumor development. The downstream targets of YAP have been shown to be highly context dependent. In this study, we used the embryonic mouse tooth germ as a tool to search for the downstream targets of YAP in ectoderm-derived tissues. Yap deficiency in the dental epithelium resulted in a small tooth germ with reduced epithelial cell proliferation. We compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 120 publications
(147 reference statements)
0
23
0
Order By: Relevance
“…Amot is part of the tension-sensing junctional complexes, while Vgll2 is a transcriptional cofactor (Maeda et al, 2002). In the facial ectoderm the Hippo pathway promotes proliferation in maturing skin and oral epithelia (Liu et al, 2015) and signaling that is necessary for survival of the underlying mesenchyme (Johnson et al, 2011). This raises the possibility that tension within the ectoderm, sensed by the Hippo pathway, might be important for coordinating growth of the mesenchyme with that of the overlying ectoderm.…”
Section: Resultsmentioning
confidence: 99%
“…Amot is part of the tension-sensing junctional complexes, while Vgll2 is a transcriptional cofactor (Maeda et al, 2002). In the facial ectoderm the Hippo pathway promotes proliferation in maturing skin and oral epithelia (Liu et al, 2015) and signaling that is necessary for survival of the underlying mesenchyme (Johnson et al, 2011). This raises the possibility that tension within the ectoderm, sensed by the Hippo pathway, might be important for coordinating growth of the mesenchyme with that of the overlying ectoderm.…”
Section: Resultsmentioning
confidence: 99%
“…In transgenic mice that overexpress a constitutively active form of YAP in the dental epithelium, the resulting tooth phenotype was deformed tooth morphogenesis with widened dental lamina [105]. In contrast, YAP deficiency in the dental epithelium resulted in development of a small tooth germ with reduced epithelial cell proliferation [106]. Data from the gene expression profiles of an embryonic E14.5 YAP conditional knockout and YAP transgenic mouse tooth germs indicate that YAP regulates the expression of Hoxa1 and Hoxc13 in oral as well as dental epithelial tissues [106].…”
Section: Prospective Of Other Wnt Signaling Moleculesmentioning
confidence: 99%
“…In contrast, YAP deficiency in the dental epithelium resulted in development of a small tooth germ with reduced epithelial cell proliferation [106]. Data from the gene expression profiles of an embryonic E14.5 YAP conditional knockout and YAP transgenic mouse tooth germs indicate that YAP regulates the expression of Hoxa1 and Hoxc13 in oral as well as dental epithelial tissues [106]. However, the relationship between Wnt signaling and YAP/TAZ in tooth formation remains to be determined.…”
Section: Prospective Of Other Wnt Signaling Moleculesmentioning
confidence: 99%
“…For example, the Hippo pathway (the Salvador‐Warts‐Hippo) is correlated with the renewal and differentiation of stem cells and it has been identified as a critical link of oncogenic transformation in NSCLC (You et al, ). In fact, YAP, as a Hippo signaling transcriptional coactivator, can greatly affect the proliferation of stem cells, the control of organ size, and the development of tumors through the regulation of downstream transcriptional target genes Ctgf and Birc5/surviving (Liu et al, ; Yeung et al, ). Additionally, a recent study reported that YAP transcriptional activity was associated with the metastasis of lung cancer (Huang et al, ).…”
Section: Discussionmentioning
confidence: 99%